(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, missing children and child abduction have happened frequently, which has sounded the alarm to every family with children. People pay more attention to the safety and physical health of children. The most common child trackers on the market are smart children’s watches, but the products lack hidden designs. Through a comparative analysis of the existing literature methodology, this study found that the safety and health of children have become one of the problems of globalization. The application will use existing GPS and GSM technology to design new products with concealment that will be friendly to the kids, and yet convenient to their parents. At the same time, it has a real-time tracking function and physical activity record to meet the needs of parents for children’s safety and health monitoring. This study will expand the theoretical knowledge and inspire practical application.